A role of Sirt1 in the Notch signalling pathway. - Horváth, Matej (Jihočeská univerzita, 2017)
The aim of this thesis was to examine role of Sirt1 in the Notch signalling pathway, using Drosophila as a model organism. Based on in vivo and in vitro studies, we conclude that Sirt1 plays a positive role in Notch signalling. In embryonic S2N cells, Sirt1 is responsible for the protection from metabolic stress-induced down-regulation of subset of E(Spl) genes. During development, Sirt1 is responsible for proper Notch-dependent specification of SOPs and wing development. Sirt1 can regulate the Notch signalling on multiple levels via deacetylation of various substrates involved in the Notch signalling revealed by our proteomic survey.
A role of Sirt1 in the Notch signalling pathway.
Keywords: Sirt1; Notch signalling; Drosophila development; metabolic sensor; S2N cells; metabolic stress; Sirt1; Notch signalling; Drosophila development; metabolic sensor; S2N cells; metabolic stress